Phytoplankton and periphyton production and its relation to temperature in a humic lagoon - Rodriguez, Patricia Laura (2015)
To analyse the existence of interactive competition between phytoplankton and periphyton, we studied their photosynthesis-irradiance (P-E) response during one year in a humic lagoon. Lake production was dominated by phytoplankton, which followed seasonal changes in temperature. Periphyton primary production and algae biomass increased in winter, when phytoplankton biomass and production were lower. In this study we show that even in conditions of phytoplankton dominance, the habitat coupling between phytoplankton and periphyton can still be noticed.